Konsultasi Gizi untuk Meningkatkan Pengetahuan Siswa Sekolah Menegah Atas tentang Gizi Seimbang - Setyaningrum Rahmawaty; Anisah Ni’mah Azizah; Ufairoh Maliha Sofwah (Universitas Muhammadiyah Surakarta, 2022)
Adolescents are vulnerable to the emergence of nutritional problems, both undernutrition and overnutrition which can influence their health and school performance. However, many of them on an improper diet to overcome their nutritional issues. The purpose of this community service was to improve high school students’ knowledge on a balanced nutrition. A nutrition counseling program was designed and implemented in 86 students in class XI at the Al-Islam High School, Surakarta. Each student received an individual nutrition consultation by a nutrition student that refers to Standardized Nutrition Care Process (SNCP). The model consists of 4 steps including nutrition assessment, nutrition diagnosis, nutrition intervention and nutrition monitoring and evaluation. Students’ knowledge on the balanced nutrition were measured before and after the counselling using a validated questionnaire consisted of 10 item questions about the balanced nutrition. Average age of the total students was 15-18 years old. Nearly approximately 50% students’ knowledge on the balance nutrition improved after the counselling in all item questions of the questionnaire. The highest improvement score is the food habit statement, while the lowest is example of dietary sources. Nutrition education about sources of nutrients is guaranteed.